Unusual linear dependency of viscosity with temperature in ionic liquid/water mixtures12. Issue 37 (12th September 2016) - Nanda, R.
Abstract : The unusual linear scaling of the self-diffusion coefficient and viscosity leads to the violation of the SE and FSE equations and shows dynamic heterogeneity. Abstract : An unusual linear dependency of viscosity with temperature has been observed in aqueous solutions of 1-octyl-3-methylimidazolium-based ionic liquids because of the ion induced structural transition which leads to the violation of both the Stokes–Einstein and fractional Stokes–Einstein equations, suggesting the presence of dynamic heterogeneity in the system.